The effect of aggregation on the viscosity of graphite nanofluids - Wong, Ting Foong. (2011)
An experimental investigation is conducted on the effect of aggregation on the viscosity of graphite water-based nanofluids. The stability of nanofluids is characterized by using the sedimentation observation and UV-vis spectrophotometer measurement. Its stability was influenced by the characteristics between suspended nanoparticles and base fluid. For the viscosity measurements, the shear thinning effect, the increased effective viscosity and the dependent of temperature were observed in this experiment is caused by agglomeration. A transmission electron microscope (TEM) was then used to reveal the dispersion and morphology of nanoparticles in base fluids. The results show that there are a lot of clusters and agglomeration due to the high surface area interaction to attract each particle. Properties and structure in a molecule vibration of graphite nanofluids have been studied using the Raman spectroscopy. The Raman spectroscopy characterizes the D and G peaks position and relative intensity with number of graphite amount. This reflects the evolution of the electronic structure and electron–phonon interactions.